ANALISIS PENGGUNAAN GADGET TERHADAP DISIPLIN BELAJAR SISWA DI SEKOLAH DASAR (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the use of gadgets on students’ learning discipline in elementary schools, identify the positive and negative impacts of gadget use, and examine efforts to improve students’ learning discipline in the era of rapid technological development. This research employs a qualitative method with a literature study approach. Data were collected from various sources such as books, scientific journals, and research articles relevant to the topic. The data collection technique used content analysis, while the data analysis was conducted by reviewing, comparing, and categorizing information based on related themes. The results show that gadget use has a significant influence on students’ learning discipline. The positive impacts include easier access to information, increased learning motivation, and more interactive learning processes. However, excessive use of gadgets can lead to negative impacts such as decreased concentration, procrastination, and low learning discipline among students. Therefore, efforts such as supervision, time limitation, and digital literacy education are needed to optimize the use of gadgets in learning. In conclusion, wise and controlled use of gadgets can support the improvement of students’ learning discipline in elementary schools.